PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA ( Studi Pada Sekolah Dasar Negeri di Kecamatan Tlogowungu Kabupaten Pati) (Students' Journal of Economic and Management, 2013)
The purpose of this study to determine the effect of principal's leadership and work motivation on elementary school teachers performance mediated by the Job Satisfaction. This research was conducted with a purposive sampling method and implemented in in the sub-district Tlogowungu Pati. The study population was all teachers Elementary School (SDN) in Sub-district Tlogowungu Pati as many as 217 teachers. The sampling technique used in this study is the purposive sampling, thus obtained a sample of 116 teachers. Method of data collection was conducted through questionnaires. Technical test data used in this study include validitas test, reliability test, classical assumption test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. Data collected was tested for validity by looking at the magnitude of the KMO value is above 0.5 and the results of factor loading above 0.4 shall be declared valid. The results of validity test demonstrate the value of KMO for principal's leadership was 0.834 with loading factor between 0.424-0.770, KMO of work motivation was 0.757 with a loading factor between 0.454-0.806. KMO for job satisfaction was 0.741 with loading factor between 0.451-0.719 and KMO for the performance was 0.856 with a loading factor between 0.687-0.781. It can be said that all the variables are declared valid. The result of Reliability test showed 0.854 for principal's leadership,0.788 for work motivation, 0.881 job satisfaction and 0.917 for performance. This shows that all the variables reliably. From the analysis and discussion show that a significant positive influence principal's leadership on job satisfaction, significantly positive effect of work motivation on job satisfaction, principal's leadership is a significant positive effect on performance, work motivation significantly positive effect on performance and job satisfaction significantly positive effect on performance. Strong influence of principal's leadership is directly compared to the performance through the mediation of job satisfaction. Moreover of work motivation has strong directly influence compared toward the performance through the mediation of job satisfaction.   Keywords: Principal's Leadership, WorkMotivation, Job Satisfaction and Performance.